Soils and Land Classification Relation in Raipur Area (M.P.) - Kolarkar, A.S. (Journal of Soil and Water Conservation, 2022)
Land classification has always been a highly controversial subject. This is so even with "Land classification" itself. There are authors using this word in a very broad geographical sense and others limiting it and making it of as specially economic nature (White, 1958, Christian 1954, Kellogg 1951). Ultimately, numerous types of land classifications have come up which must be distinguished properly as was described by Vink (1960). However, there is no dispute about the fact that all the good land classifications are based on good soil classification. A good soil survey, consisting not only of a well made soil map, but also a good description of soils mapped must always be made before scientifically sound classification in any categories from I to VIII can be made. One has always to keep in mind that land classification to some extent reflects in land appraisal or in comparable value of qualitative differences of 'soils' conditioned by natural properties and agricultural practices.